(untitled) (International Journal of Engineering and Computer Science, 2014)
Sensor network is having its importance in many real time applications to sense different atmospheric, environmental, industrial features. Sensor network is generally a hybrid network with large number of sensor nodes. These sensor nodes are defined with energy parameters and consume some amount of energy with each transmission, receiving and forwarding activity. These sensor networks are present under different network organizing architectures. One of such architecture is the clustered sensor network in which complete network is divided in small segments called clusters. Network is having the multiple sinks that can be defined in any cluster over the network as well as having the randomized node movement. Each cluster also having the static sink as well as having the Cluster head to control the communication. In this paper, a cluster analysis approach respective to the mobile sink node identification is defined to perform the load balancing over the network. The work will check for the presence of the mobile sink in each cluster